2022
DOI: 10.1108/sej-01-2022-0001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility expectations on purchase intention of social enterprise products

Abstract: Purpose With the rapid increase in corporate social responsibility (CSR) practices in many firms and the development of social enterprises (SE), questions regarding the ways in which CSR affects consumers’ attitudes and behaviours have become crucial. This study aims to investigate how consumers’ CSR expectations and knowledge relate to their attitudes and purchase intentions regarding SE products. Design/methodology/approach This study investigates how consumer expectations of CSR and their own social respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…These studies found that legal CSR activities were indeed associated with increased purchase intention, but only when those activities were perceived as genuine. If consumers felt that a company was engaging in legal CSR activities to gain favor or avoid negative publicity, they were less likely to buy from it (Ng, 2022;Vu et al, 2022;Zhuang et al, 2022). Voluntary compliance with all applicable rules and regulations enhances the organization's image in customers' minds (Carroll, 1991b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies found that legal CSR activities were indeed associated with increased purchase intention, but only when those activities were perceived as genuine. If consumers felt that a company was engaging in legal CSR activities to gain favor or avoid negative publicity, they were less likely to buy from it (Ng, 2022;Vu et al, 2022;Zhuang et al, 2022). Voluntary compliance with all applicable rules and regulations enhances the organization's image in customers' minds (Carroll, 1991b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, Schill and Godefroit-Winkel (2021) examined the influence of CSR on consumer emotions which in turn influence CA towards the shopping mall. Most recently, Ng (2022) investigated how perceived CSR relate to CA regarding social enterprise products and found positive effects. Both Stadlthanner et al (2022) and Lee and Lin (2022) studied how CSR advertisements affect CA and found a positive significant influence.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%